Examining the Fluctuation of Soil Organic Carbon Levels: An Analysis of the Shuklaphanta National Park in Nepal - Rajeev Joshi; Mamta Bhatta (Applied and Environmental Soil Science)
Soil organic carbon (SOC) is a crucial carbon reservoir that needs to be monitored for deforestation and forest degradation. The top one-meter layer of soil contains around 1500–1600 Pg of carbon. Assessing the SOC pool is essential for understanding the soil system’s carbon sequestration potential (CSP) as a mitigation strategy and determining whether it acts as a source or sink for atmospheric CO2, depending on the level of saturation. However, there are limited studies on SOC in Nepal’s forests. This research aims to assess SOC variation in the Shuklaphanta National Park in Nepal. It focuses on determining SOC according to depth and analyzing the variation of SOC among the core area of the national park, grasslands, and buffer zone community forests (CFs) and identifying the factors that contribute to the variation in soil carbon across different land uses. The study was conducted using a systematic sampling method with a sampling intensity of 6.59% on 180 soil samples taken from permanent plots set up by the Forest Resource Assessment (FRA) Nepal. The analysis was based on SOC estimated up to the depth of 0–10, 11–20, and 21–30 cm using a modified Walkley–Black wet oxidation method. The study also analyzed contributing factors affecting soil carbon such as vegetation, forest fire, rate of forest resource use, and different soil properties like pH and bulk density. The study found that the mean SOC% up to the depths of 0–10 cm, 11–20 cm, and 21–30 cm was 2.08, 0.98, and 0.68, respectively, in forest areas. Mean SOC% in grasslands was found to be 1.7, 1.68, and 1.87 in 0–10, 11–20, and 21–30 cm, respectively, and in community forests, it was found to be 1.3, 0.98, and 0.58 in 0–10, 11–20, and 21–30 cm, respectively. Similarly, the vertical mean SOC in tC⋅ha−1 (0–30 cm) was found to be 41.75 tC·ha−1 in the core area of the national park, 46.64 tC·ha−1 in grassland, and 37.50 tC·ha−1 in CFs. The study also found that there was variation in SOC with depth and that most of the SOC was concentrated in the topsoil in the core area of the national park and buffer zone community forests. Deep layers of SOC were found in grasslands, core area of the national park, and CF in decreasing order. The study implies that the national park has enormous potential to recapture atmospheric CO2 into the soil. Participating in the sustainable management of the national park can enhance the soil quality and help meet strategies to mitigate climate change. Factors such as vegetation cover, fire, bulk density, and vegetation type were found to be promising for SOC concentration.